Light-triggered release of ciprofloxacin from an in situ forming click hydrogel for antibacterial wound dressings. Issue 45 (26th October 2015) - Shi, Yue; Truong, Vinh X.; Kulkarni, Ketav; Qu, Yue; Simon, George P.; Boyd, Richard L.; Perlmutter, Patrick; Lithgow, Trevor; Forsythe, John S.
Abstract : Light triggered release of an antibiotic from a click crosslinked hydrogel was developed by conjugating ciprofloxacin through a photo-cleavable linker to the hydrogel network structure. Abstract : Light triggered release of an antibiotic from a click crosslinked hydrogel was developed by conjugating ciprofloxacin through a photo-cleavable linker to the hydrogel network structure. Upon irradiation of the hydrogel material with UV light (365 nm) at low intensity, native ciprofloxacin was released into the surrounding environment and could be detected by HPLC. The antimicrobial activity of the released compound on Staphylococcus aureus was demonstrated.